rbioapi: user-friendly R interface to biologic web services' API - Rezwani, Moosa; Pourfathollah, Ali Akbar; Noorbakhsh, Farshid (Bioinformatics (Oxford, England), 2022)
Many packages serve as an interface between R language and the Application Programming Interface (API) of databases and web services. There is usually a 'one-package to one-service' correspondence, which poses challenges such as consistency to the users and scalability to the developers. This, among other issues, has motivated us to develop a package as a framework to facilitate the implementation of API resources in the R language. This R package, rbioapi, is a consistent, user-friendly and scalable interface to biological and medical databases and web services. To date, rbioapi fully supports Enrichr, JASPAR, miEAA, PANTHER, Reactome, STRING and UniProt. We aim to expand this list by collaborations and contributions and gradually make rbioapi as comprehensive as possible. rbioapi is deposited in CRAN under the https://cran.r-project.org/package=rbioapi address. The source code is publicly available in a GitHub repository at https://github.com/moosa-r/rbioapi/. Also, the documentation website is available at https://rbioapi.moosa-r.com. Supplementary data are available at Bioinformatics online.